Ethno-Cultural Identity Formation in Mapuche Youth Biographies: A Case Study from the Perspective of Colonial and Transgenerational Historical - Garcés Pérez, Gabriela; Sagner-Tapia, Johanna; Alarcón, Ana M. (Journal of Ethnic and Cultural Studies, 2024)
In this paper, we present evidence from a case study exploring the intricate relationship between transgenerational historical and colonial trauma and the process of ethno-cultural identity formation among young Mapuche individuals residing in rural communities in Chile. Our analysis centers on two prominent themes derived from their personal narratives, shedding light on the intergenerational dynamics that significantly influence the current development of their ethno-cultural identities. These themes are the communication and transmission of family history and memory, and the valuation of Mapuche culture. Our methodology employs biographical narratives and adopts a grounded theory approach, specifically in its constructivist variant. The findings of this study reveal that the biographies of these young individuals reflect distinct elements of emotional impact and coping strategies linked to historical and colonial trauma, which are transmitted across generations. In one case, there appears to be a tendency to conceal family history, while in the other, active preservation of memory seems to underpin reflections on identity, belonging, and the appropriation of Mapuche culture. Furthermore, our analysis highlights the significance of emotional connections with family, as well as individual expectations and future aspirations, which play pivotal roles in shaping motivations and expressions concerning Mapuche ethno-cultural affiliation or disassociation. We contend that these intricate dynamics mediate the formation of ethno-cultural identity among Mapuche young people.